Role of Grants for Tourism Purposes in Development of the Northern Great Plain Region - Darabos, Éva; Nagy, Tünde Orsolya (International Journal of Engineering and Management Sciences, 2018)
Aim of the treatise is, based on main macroeconomic indicators, to present the development of the Northern Great Plain region and the amount of EU grants received, including the ones for tourism purposes, as well as to examine the effects of grants. Based on the data, it can be concluded the region received significant grants during the years 2007-2013; it is in last place in view of the economic development but has achieved better performance in several areas. It is difficult to examine the accommodation and food service national economic sector independently: in one respect, it develops by the combined impact of several other areas, on the other hand, the tourism-related developments become usable for other sectors as well, new enterprises and investments are launched, at the same time, not only the companies’ but the municipalities’ revenues from tourism are increasing. Based on the statistical data, attention will be drawn to the fact that the outcome of developments is just moderate in the area of catering and tourism in the region and has a different rate by county.